2017
DOI: 10.1007/s00345-017-2123-4
|View full text |Cite
|
Sign up to set email alerts
|

How to accelerate the upper urinary stone discharge after extracorporeal shockwave lithotripsy (ESWL) for < 15 mm upper urinary stones: a prospective multi-center randomized controlled trial about external physical vibration lithecbole (EPVL)

Abstract: EPVL is a noninvasive, effective, and safe adjunctive treatment which increases and accelerates upper urinary stones discharge after ESWL treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…However, there still lack reported studies showing the precise effect of EPVL treatment after ESWL therapy for upper ureteric stones 1.0-2.0 cm in size. Although, in their other study [27] they evaluated the efficacy of EPVL in patients with upper ureteric stones, the sample size was relatively small compared with our center. Therefore, we conducted this prospective, randomized study in our center.…”
Section: Discussionmentioning
confidence: 94%
“…However, there still lack reported studies showing the precise effect of EPVL treatment after ESWL therapy for upper ureteric stones 1.0-2.0 cm in size. Although, in their other study [27] they evaluated the efficacy of EPVL in patients with upper ureteric stones, the sample size was relatively small compared with our center. Therefore, we conducted this prospective, randomized study in our center.…”
Section: Discussionmentioning
confidence: 94%
“…It is very clear and concise that for any newly designed and introduced technique to be well accepted, it should be first safe and also efficacious. Related with this issue, data obtained from several clinical studies have proved well with high-level evidence that the EPVL is a safe, simple, effective, and non-invasive method to facilitate the spontaneous passage of the residual fragments detected after RIRS or ESWL [2][3][4][5][6]. Of the published data with this system so far, Wu et al [2] were able to demonstrate that EVPL as a supplement to RIRS could be more effective than RIRS alone by shortening the time period for stone clearance, increasing complete stone-free rates with good patient compliance and acceptance.…”
mentioning
confidence: 82%
“…Further supporting these findings, Zhang et al [5] were able to show that the best time to perform EPVL is 3 days after RIRS procedure for the highest stone-free rates at any point in time with meaningfully reduced complications caused by these fragments. Last but not least, in their original studies, Long et al [3], Wu et al [6], and Tao et al [4], all reported well that EPVL could facilitate the spontaneous discharge of residual stone fragments with a meaningfully shortened expulsion time after SWL. Thus all these data clearly indicate that the EPVL system can be regarded as an adjunctive active treatment modality particularly for residual stone fragments after RIRS and SWL procedures in an outpatient service manner.…”
mentioning
confidence: 98%
“…As listed in Table 1, a total of 8 prospective studies published from 2001 to 2019 were finally enrolled into the present analysis [29,[32][33][34][35][36][37][38], including 7 RCTs and 1 prospective case control study. Three studies were multi-center studies (NCT02645708, NCT02643134, one not registered).…”
Section: Characteristics and Quality Of The Included Studiesmentioning
confidence: 99%